Astrocyte-Specific Overexpression of Nrf2 Delays Motor Pathology and Synuclein Aggregation throughout the CNS in the Alpha-Synuclein Mutant (A53T) Mouse Model - Gan, Li (Society for Neuroscience, 2012)
Alpha synuclein (SYN) is a central player in the pathogenesis of sporadic and familial Parkinson's disease (PD). SYN aggregation and oxidative stress are associated and enhance each other's toxicity. It is unknown whether the redox-sensitive transcription factor nuclear factor erythroid 2-related factor 2 (Nrf2) plays a role against the toxicity of SYN. To examine this, mice selectively overexpressing Nrf2 in astrocytes (GFAP-Nrf2) were crossed with mice selectively expressing human mutant SYN (hSYN(A53T)) in neurons. Increased astrocytic Nrf2 delayed the onset and extended the life span of the hSYN(A53T) mice. This correlated with increased motor neuron survival, reduced oxidative stress, and attenuated gliosis in the spinal cord, as well as a dramatic decrease in total hSYN(A53T) and phosphorylated (Ser129) hSYN(A53T) in Triton-insoluble aggregates. Furthermore, Nrf2 in astrocytes delayed chaperone-mediated autophagy and macroautophagy dysfunction observed in the hSYN(A53T) mice. Our data suggest that Nrf2 in astrocytes provides neuroprotection against hSYN(A53T)-mediated toxicity by promoting the degradation of hSYN(A53T) through the autophagy-lysosome pathway in vivo. Thus, activation of the Nrf2 pathway in astrocytes is a potential target to develop therapeutic strategies for treating pathologic synucleinopathies including PD.